THE ROLE OF GRAMMAR GAMES IN ENHANCING ENGLISH LANGUAGE SKILLS: A SYSTEMATIC LITERATURE REVIEW - Ratu Nidaul Inayah; Lutvia Febrianti; Nafan Tarihoran (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Grammar games have become an effective pedagogical tool in teaching English, providing an engaging and interactive alternative to traditional grammar instruction. This systematic review uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) framework. Findings from 11 empirical studies published between 2019-2024, sourced from ScienceDirect (5), Mendeley (3), PubMed (3). explores the role of grammar games in enhancing English language skills, particularly in improving grammar comprehension, motivation, and retention among learners. By analyzing previous research, this study highlights the advantages of both digital and traditional grammar games in fostering student engagement and active participation. Findings indicate that grammar games promote meaningful learning experiences, reduce anxiety, and encourage collaborative learning. Additionally, integrating gamification elements, such as rewards and challenges, enhances learners' motivation and overall language proficiency. While digital games offer instant feedback and personalized learning paths, traditional games provide face-to-face communication and kinesthetic learning opportunities. The study concludes that combining digital and conventional grammar games can optimize grammar instruction, making language learning more effective and enjoyable.